MIDDLE‐CLASSNESS AND WHITENESS IN PARENTS’ RESPONSES TO MULTICULTURALISM: A STUDY OF ONE SCHOOL - Levine‐Rasky, Cynthia (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
Since its founding in 1941 until the 1980s, “Pinecrest” School was dominated by child‐ ren from “Baywoods,” an economically privileged and largely Jewish neighbourhood. In the late 1980s, the population of the school changed to include children of immigrants in an adjacent neighbourhood, “Kerrydale.” Seeking to protect their children’s cultural capital and class advantages, the Baywoods parents’ response involved the construction of fundamental difference and concerns about effects on school quality. The responses were interrupted by dilemma and ambivalence. They are read through the intersections of middle‐class formation and whiteness in terms of three dimensions: practice, relationality, and maintenance. Key words: Jews, immigrants, public school, parents, exclusion, social class, ethnicity Depuis sa création en 1941 jusque dans les années 1990, l’école « Pinecrest » accueillait principalement des enfants de « Baywoods », un quartier habité par des familles à l’aise et surtout par des Juifs. À la fin des années 1980, la population de l’école a changé à la suite de l’intégration d’enfants d’immigrants provenant de « Kerrydale », un quartier voisin. Cherchant à protéger le capital culturel de leurs enfants et les avantages de leur classe sociale, les parents de Baywoods ont réagi en invoquant la notion de différence fondamentale et en se préoccupant des effets possibles sur la qualité de l’école. Dilemmes et ambivalence ont toutefois interrompu le processus. Les réactions des parents sont interprétées dans le contexte du lien entre la formation de la classe moyenne et la blancheur et ce, à trois niveaux : la pratique, les relations et le maintien de la reproduction du groupe. Mots clés: Juifs, immigrants, école publique, parents, exclusion, classe sociale, ethnicité